2018
DOI: 10.22159/ijpps.2018v10i4.24100
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combination of Two Plant Extracts on Diabetes Mellitus

Abstract: Objective: To investigate the anti-diabetic activity of combined ethanolic extracts (1:1mixture) of dry leaves of Syzygium cumini and Psidium guajava belonging to the family Myrtaceae as well as to compare the anti-diabetic activity of these plants by in vitro methods.Methods: In vitro glucose uptake assay was performed on cultured L6 cell lines (rat myoblast cell line) and estimated the glucose uptake using high sensitivity glucose oxidase kit. In vitro alpha amylase inhibitory assay was performed on porcine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Diabetes mellitus (DM) which is one of the public health issues is a metabolic disorder characterized by the presence of chronic hyperglycemia accompanied by an impairment of carbohydrate, lipid, and protein metabolism that can lead to premature death [13].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus (DM) which is one of the public health issues is a metabolic disorder characterized by the presence of chronic hyperglycemia accompanied by an impairment of carbohydrate, lipid, and protein metabolism that can lead to premature death [13].…”
Section: Discussionmentioning
confidence: 99%
“…Spirulina, a microscopic, filamentous, dried biomass of Arthrospira plantesis, is an oxygenic photosynthetic cyanobacterium found in fresh and marine waters worldwide [1]. It is consumed by both humans and animals as a food supplement [2,3]. Spirulina has been labeled as a superfood because of its richness in carbohydrates, proteins, sterols, polyunsaturated fatty acids and minerals such as selenium, calcium, chromium, iron, manganese, zinc and magnesium [4].…”
Section: Introductionmentioning
confidence: 99%
“…Synergism between plant extracts has been considered in the development of many pharmaceutical products such as diabetes mellitus and infectious diseases [71][72][73] . A recent report also suggested that a combination of the extracts of Cornus officinalis, Rosa multiflora, Lespedeza bicolor, Platycladus orientalis, and Castanea crenata showed preventive effects on atopic dermatitis-like skin lesions 74 .…”
Section: Discussionmentioning
confidence: 99%